Unmanned aerial vehicle 3D printing concrete material and preparation method and application thereof
By optimizing the formula of 3D printed concrete materials and combining the transportation capacity of the drone, the problems of high density and poor endurance of traditional materials are solved, and lightweight, high-strength and self-cleaning concrete materials are realized. They are suitable for 3D printing of drones and meet the multiple performance needs of building structures.
Patent Information
- Application Number
- CN202510064795.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-04-15
AI Technical Summary
Traditional 3D printing materials are denser, which is difficult to meet the battery life requirements of the materials that drones can carry. At the same time, the strength and printability indicators are poor during the printing process.
A drone 3D printed concrete material is used, and its formulation includes cement, fly ash, sand and gravel, ultrafine mineral microbeads, mineral powder, water reducing agent, thickening rheology agent, early strength agent, defoaming agent, graphene and nanotitanium dioxide particles. By optimizing the formulation and adding catalysts, the fluidity and strength of the material are improved.
It realizes the lightweight, high strength and self-cleaning characteristics of the material, ensuring that the printed concrete of the drone can maintain printability and mechanical indicators without affecting the conditions of lightweight and low density, and provides self-cleaning functions, suitable for structures such as building exterior walls and bridges.
Smart Images

Figure BDA0005243928310000101 
Figure BDA0005243928310000111 
Figure BDA0005243928310000121
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of building 3D printing, and in particular to a drone 3D printing concrete material and a preparation method and application thereof. Background Art
[0002] 3D printing is a type of rapid prototyping technology, also known as additive manufacturing. It is a technology that uses digital model files as the basis, uses powdered metal or plastic and other bondable materials to construct objects by printing layer by layer. 3D printing is usually achieved by using digital technology material printers. It is often used to make models in the fields of mold manufacturing and industrial design, and then gradually used for the direct manufacturing of some products. It has been widely used in jewelry, footwear, industrial design, architecture, engineering and construction, automobiles, aerospace and medical industries, education, geographic information systems, civil engineering, guns and other fields. With the continuous updating and development of computer technology, material technology and other technologies, 3D printing technology will surely usher in great development and push the manufacturing industry to a new level.
[0003] In recent years, 3D printing technology has begun to flourish in China. In the traditional 3D printing construction industry, the requirements for site environment and equipment are high. These traditional large-scale equipment systems used for printing need to be connected to the power supply and are not agile and flexible enough. For example, when inspecting and repairing tasks or working in remote and harsh environments, large-scale printing equipment seems to be unable to cope with it. It is difficult to transport or install large equipment in these environments. In this regard, drones have natural advantages in these aspects. Drones are small and flexible. Under the control of computer systems, they can fully complete various complex flight instructions. They are not restricted by the tracks of traditional motion systems, and can also reach environments that are difficult for large equipment to reach for 3D printing operations. However, for drones, the density of traditional 3D printing materials is relatively high, and it is difficult to meet the endurance requirements of the materials that drones can carry.
[0004] Therefore, there is a need for lighter 3D printing concrete materials for use based on drone designs, while also ensuring that the strength of other indicators of the new material in printing is not affected. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide a drone 3D printing concrete material and a preparation method and application thereof. The 3D printing concrete material has the characteristics of light weight, high strength and self-cleaning, and has good fluidity before printing, ensuring that the printability, mechanics and other indicators of the drone-printable concrete are not affected under the conditions of light weight and low density. At the same time, it also has a certain supporting strength and can support the printing of subsequent layers.
[0006] The present invention adopts the following technical solutions to solve the above technical problems:
[0007] A drone 3D printing concrete material comprises the following raw materials in parts by weight: 20 to 45 parts of cement, 5 to 15 parts of fly ash, 16 to 40 parts of sand and gravel, 1 to 10 parts of ultrafine mineral microbeads, 0.5 to 15 parts of mineral powder, 0.5 to 2.5 parts of water reducing agent, 0.01 to 0.05 parts of thickening rheological agent, 0.1 to 1 parts of early strength agent, 0.02 to 0.05 parts of defoaming agent, 0.1 to 0.5 parts of graphene, 0.5 to 2 parts of nano titanium dioxide particles, and 20 to 30 parts of water.
[0008] As one of the preferred embodiments of the present invention, the cement is silicate cement with a strength grade of ≥42.5 and a specific surface area of 300 to 400 m 2 / kg.
[0009] As one of the preferred embodiments of the present invention, the fly ash is secondary fly ash with a fineness of 14 to 25 μm.
[0010] As one of the preferred embodiments of the present invention, the sand and gravel are well-graded machine-made sand with a particle size range of 0.075 to 5.0 mm and an apparent density of 2000 to 2900 kg / m 3 This range of machine-made sand not only meets the grading requirements, but is also the key to reducing the density of concrete.
[0011] As one of the preferred embodiments of the present invention, the ultrafine mineral microbeads have a fineness of d50≤3μm, a water content of 0.1% to 1.0%, a 0.045mm sieve residue of 5% to 10%, and a water requirement ratio of 80% to 98%. The ultrafine mineral microbeads can improve the pore structure of 3D printed concrete, and improve the density and impermeability of concrete.
[0012] As one of the preferred embodiments of the present invention, the density of the mineral powder is 2.5 to 3.5 g / cm 3 , specific surface area 500~650m 2 / kg, fluidity ratio 95%~110%, water content 0.3%~0.9%. Mineral powder improves the comprehensive performance of 3D printing concrete, reduces hydration heat, and prevents temperature cracks.
[0013] As one of the preferred embodiments of the present invention, the water reducing agent is a polycarboxylic acid type water reducing agent with a solid content of 30% to 50% and a water reduction rate of 20% to 50%. The water reducing agent can reduce the amount of cement and improve the fluidity and strength of 3D printed concrete.
[0014] As one of the preferred embodiments of the present invention, the thickening rheological agent is a mixture of a sodium cellulose thickening rheological agent and xanthan gum in a ratio of 1:1; wherein the viscosity of the sodium cellulose is 90,000 to 120,000 mPa·s, and the drying weight loss rate is ≤6.0%; the viscosity of a 1% aqueous solution of xanthan gum (25°C) is ≥500 mPa·s. By using the above two mixtures for thickening, the sodium cellulose thickening rheological agent ensures that the concrete material has a certain consistency while still having the required fluidity; the xanthan gum solution has the characteristics of low concentration and high viscosity, and it forms a gel state when in contact with water, and cross-linking occurs between the molecular chains to form a three-dimensional network structure, which reduces the fluidity of the mortar, thereby achieving a thickening effect. The mixture thickening system can ensure the compactness and filling of the concrete, and quickly stabilize the unstable concrete system.
[0015] As one of the preferred embodiments of the present invention, the early strength agent is a mixture of one or more of sodium sulfate, calcium formate, sodium carbonate and gypsum, with a moisture content of ≤5.0% and a 1.18 mm sieve residue of ≤1.0%. The early strength agent improves the early strength of concrete and has a significant effect on the constructability of 3D printing during printing operations.
[0016] As one of the preferred embodiments of the present invention, the defoamer is a polyether defoamer, and the mass concentration of the solution is 0.2-0.5 parts per million. The polyether defoamer can effectively eliminate bubbles generated during the operation.
[0017] As one of the preferred embodiments of the present invention, the graphene is a two-dimensional material composed of a single layer of carbon atoms, with a size of less than 5 μm and a moisture content of 0.1% to 0.5%. Graphene has strong chemical inertness and can maintain its performance in harsh environments, thereby ensuring the long-term stability of concrete.
[0018] As one of the preferred embodiments of the present invention, the nano titanium dioxide particles have a particle size of 10-100 nm and a moisture content of ≤0.5%. The nano titanium dioxide particles can impart a self-cleaning function to the concrete surface, and the photocatalytic effect generated under ultraviolet light can decompose surface organic pollutants.
[0019] A method for preparing the above-mentioned drone 3D printing concrete material comprises the following steps:
[0020] (1) Add the formulated amount of cement, fly ash, sand and gravel, ultrafine mineral beads, and mineral powder into a blender and pre-mix for 50 to 80 seconds to obtain a mixed material A;
[0021] (2) Add the formulated amount of water reducer, early strength agent and defoamer into the formulated amount of water and stir for 60 to 80 seconds to obtain a mixed material B;
[0022] (3) After mixing the mixed material A and the mixed material B, add the thickening rheological agent in the formula amount and continue stirring for 60 to 90 seconds;
[0023] (4) Continue to add the pre-prepared graphene and nano-titanium dioxide particles and stir for 60 seconds to obtain the desired drone 3D printing concrete material.
[0024] An application of the above-mentioned drone 3D printing concrete material in drone 3D printing.
[0025] Design principle:
[0026] The components in the concrete material formula for drone 3D printing of the present invention cooperate with each other, redesign the concrete material formula, and add some catalysts to ensure that the printability of the material is more prominent, ensuring that the strength and other indicators of the concrete building layer printed by using the concrete material are not affected. Among them, by combining the excellent conductivity and mechanical properties of graphene with the photocatalysis of specific nanoparticles, when the concrete surface is exposed to sunlight or ultraviolet rays, the photocatalytic nanoparticles can excite electrons and holes, decompose organic pollutants, and eliminate surface pollutants such as dust and oil stains, which can give the concrete a self-cleaning function.
[0027] The advantages of the present invention compared to the prior art are:
[0028] (1) The present invention reduces the sand and gravel content and reasonably optimizes other components, making it lighter than ordinary concrete materials, thereby greatly improving the endurance of drones carrying the material for 3D printing;
[0029] (2) The printing indexes of the present invention are basically not affected compared with those of ordinary concrete materials. The introduction of graphene mainly improves the mechanical properties and crack resistance of concrete, and enhances the density of cement paste and improves its anti-seepage ability through its flaky structure.
[0030] (3) The nanoparticles of the present invention provide a self-cleaning function for concrete through their photocatalytic effect; this self-cleaning 3D printed concrete can be widely used in structures such as building exterior walls and bridges that are exposed outdoors for a long time, and is particularly suitable for areas with severe pollution, such as urban buildings or highway protection facilities. Through the application of this innovative material, the subsequent maintenance cost can be reduced and the service life of the structure can be extended;
[0031] In summary, the composite material of the present invention has the characteristics of light weight, high strength and self-cleaning, and is suitable for 3D printing concrete structures (it has good fluidity before printing, ensuring that the printability, mechanics and other indicators of the concrete printable by drones are not affected under the conditions of light weight and low density, and it also has a certain supporting strength to support the printing of subsequent layers), especially for buildings that require self-cleaning, crack resistance and durability, which meets the various performance requirements of drone-printed buildings and has broad application prospects. DETAILED DESCRIPTION
[0032] The following is a detailed description of an embodiment of the present invention. This embodiment is implemented on the premise of the technical solution of the present invention, and a detailed implementation method and a specific operation process are given, but the protection scope of the present invention is not limited to the following embodiment.
[0033] Unless otherwise specified, the experimental methods used in the examples of the present invention are all conventional methods; the raw materials and reagents used in the examples of the present invention, unless otherwise specified, can be obtained from commercial channels; the examples of the present invention specifically use the following raw materials:
[0034] Cement: silicate cement, po42.5, specific surface area 300~400m 2 / kg.
[0035] Fly ash: Use secondary fly ash with a fineness of 14 to 25 μm.
[0036] Sand and gravel: Use well-graded machine-made sand with a particle size range of 0.075-5.0 mm and an apparent density of 2000-2900 kg / m 3 .
[0037] Ultrafine mineral microbeads: Bentonite microbeads are used, with a fineness of d50≤3μm, a moisture content of 0.1% to 1.0%, a 0.045mm sieve residue of 5% to 10%, and a water requirement ratio of 80% to 98%.
[0038] Mineral powder: density 2.5~3.5g / cm 3 , specific surface area 500~650m 2 / kg, fluidity ratio 95% ~ 110%, water content 0.3% ~ 0.9%.
[0039] Water reducing agent: Use polycarboxylic acid type water reducing agent with solid content of 30% to 50% and water reduction rate of 20% to 50%.
[0040] Thickening rheological agent: A mixture of cellulose sodium salt thickening rheological agent and xanthan gum in a ratio of 1:1; wherein the viscosity of cellulose sodium salt is 90000-120000 mPa·s, and the drying loss rate is ≤6.0%; the viscosity of 1% aqueous solution of xanthan gum (25°C) is ≥500 mPa·s.
[0041] Early strength agent: A mixture of one or more of sodium sulfate, calcium formate, sodium carbonate and gypsum, with a moisture content ≤5.0% and a 1.18mm sieve residue ≤1.0%.
[0042] Defoaming agent: Use polyether defoaming agent with a solution mass concentration of 0.2 to 0.5 parts per million.
[0043] Graphene: A two-dimensional material composed of a single layer of carbon atoms, with a size of less than 5μm and a water content of 0.1% to 0.5%.
[0044] Nano titanium dioxide particles: particle size is 10-100nm, water content ≤0.5%.
[0045] Example 1
[0046] A drone 3D printing concrete material of the present embodiment includes the following raw materials in parts by weight: 20 parts of silicate cement, 5 parts of fly ash, 16 parts of sand and gravel, 1 part of ultrafine mineral beads, 0.5 parts of mineral powder, 0.5 parts of water reducer, 0.01 parts of thickening rheological agent, 0.1 parts of sodium carbonate (early strength agent), 0.02 to 10 parts of defoaming agent, 0.1 parts of graphene, 0.5 parts of nano titanium dioxide particles, and 20 parts of water.
[0047] Preparation method:
[0048] (1) Add the formulated amount of silicate cement, fly ash, sand and gravel, ultrafine mineral beads, and mineral powder into a blender and pre-mix for 50 to 80 seconds to obtain a mixed material A;
[0049] (2) Add the formulated amount of water reducer, early strength agent and defoamer into the formulated amount of water and stir for 60 to 80 seconds to obtain a mixed material B;
[0050] (3) After mixing the mixed material A and the mixed material B, add the thickening rheological agent in the formula amount and continue stirring for 60 to 90 seconds;
[0051] (4) Add the pre-prepared graphene suspension, then add the nano-titanium dioxide particle suspension, and continue stirring for 60 seconds to obtain the desired drone 3D printing concrete material.
[0052] Example 2
[0053] A drone 3D printing concrete material of the present embodiment includes the following raw materials in parts by weight: 30 parts of silicate cement, 10 parts of fly ash, 25 parts of sand and gravel, 5 parts of ultrafine mineral beads, 7 parts of mineral powder, 1.5 parts of water reducer, 0.05 parts of thickening rheological agent, 0.5 parts of calcium formate (early strength agent), 0.03 parts of defoaming agent, 0.3 parts of graphene, 1 part of nano titanium dioxide particles, and 22 parts of water.
[0054] The preparation method is the same as Example 1.
[0055] Example 3
[0056] A drone 3D printing concrete material of the present embodiment includes the following raw materials in parts by weight: 40 parts of silicate cement, 10 parts of fly ash, 20 parts of sand and gravel, 2.5 parts of ultrafine mineral beads, 15 parts of mineral powder, 2.5 parts of water reducer, 0.05 parts of thickening rheological agent, 0.5 parts of sodium sulfate (early strength agent), 0.02 parts of defoaming agent, 0.3 parts of graphene, 1 part of nano titanium dioxide particles, and 20 parts of water.
[0057] The preparation method is the same as Example 1.
[0058] Example 4
[0059] A drone 3D printing concrete material of the present embodiment includes the following raw materials in parts by weight: 45 parts of silicate cement, 15 parts of fly ash, 40 parts of sand and gravel, 10 parts of ultrafine mineral beads, 15 parts of mineral powder, 2.5 parts of water reducer, 0.04 parts of thickening rheological agent, 1 part of gypsum (early strength agent), 0.05 parts of defoaming agent, 0.5 parts of graphene, 2 parts of nano titanium dioxide particles, and 30 parts of water.
[0060] The preparation method is the same as Example 1.
[0061] Example 5
[0062] In this embodiment, a method for applying the above-mentioned drone 3D printing concrete material is to add the prepared concrete material into the concrete extrusion system of the drone, and the extrusion rate of the extrusion system is about 1000cm 3 / h~3000cm 3 / h, the nozzle diameter is between 5cm and 15cm, and the torque range is about 10N·m to 15N·m. Start printing the concrete building layer. After that, the concrete specimen is coated and cured at room temperature for 24h, and then placed in a standard curing room for 7 to 28 days to obtain the finished concrete product. The standard curing room conditions are 18 to 22℃ and the relative humidity is 90 to 95%.
[0063] Comparative Example 1
[0064] The raw material formula and preparation of a concrete material in this comparative example are basically the same as those in Example 3, the main difference being that no fly ash is added.
[0065] Comparative Example 2
[0066] The raw material formula and preparation of a concrete material in this comparative example are basically the same as those in Example 3, the main difference being that no ultrafine mineral microbeads are added.
[0067] Comparative Example 3
[0068] The raw material formula and preparation of a concrete material in this comparative example are basically the same as those in Example 3, the main difference being that no water reducing agent is added.
[0069] Comparative Example 4
[0070] The raw material formula and preparation of a concrete material in this comparative example are basically the same as those in Example 3, the main difference being that no thickening rheological agent is added.
[0071] Comparative Example 5
[0072] The raw material formula and preparation of a concrete material in this comparative example are basically the same as those in Example 3, the main difference being that no early strength agent is added.
[0073] Comparative Example 6
[0074] The raw material formula and preparation of a concrete material in this comparative example are basically the same as those in Example 3, the main difference being that no defoaming agent is added.
[0075] Comparative Example 7
[0076] The raw material formula and preparation of a concrete material in this comparative example are basically the same as those in Example 3, with the main difference being that no graphene is added.
[0077] Comparative Example 8
[0078] The concrete material of this comparative example has the same raw material formula and preparation as those of Example 3, the main difference being that no nano titanium dioxide particles are added.
[0079] Comparative Example 9
[0080] The raw material formula and preparation of a concrete material in this comparative example are basically the same as those in Example 3, with the main difference being that no graphene and nano-titanium dioxide particles are added.
[0081] Experimental Example 1
[0082] This experimental example is used to verify the performance of the concrete material of the present invention.
[0083] 1. Experimental Methods
[0084] 1. Printability
[0085] (1) Liquidity
[0086] According to the "Determination of fluidity of cement mortar" GB / T 2419, the concrete materials of Examples 1 to 4 were tested respectively within 25±1s, and the average diameters of the mortar in two vertical directions were unfolded after the jumping table jumped 25 times to indicate the fluidity.
[0087] (2) Extrudability
[0088] The concrete materials of Examples 1 to 4 were used to continuously print a tear-free printed strip with a length of ≥2000 mm and a layer thickness of ≥10 mm. The width and thickness of the printed strip at 5 different positions with an interval of not less than 200 mm were measured, and the average value was calculated to indicate the extrudability.
[0089] (3) Opening hours
[0090] Using the concrete mixtures of Examples 1 to 4, strips with a length of ≥2000 mm were printed at intervals of 10 minutes, and the time corresponding to when the printed strips were interrupted or discontinuous was recorded to indicate the open time.
[0091] (4) Constructivity
[0092] The concrete materials of Examples 1 to 4 were used to continuously print closed loops of two layers, and the highest height of the printed body before collapse or deformation occurred was measured to demonstrate the constructability.
[0093] 2. Strength performance
[0094] A universal testing machine was used to perform stress tests on the concrete specimens obtained corresponding to the concrete materials of Examples 1 to 4, with a loading method of 50 n / s.
[0095] 3. Self-cleaning performance
[0096] The organic pollutants (1g oil) were applied to the concrete samples of Examples 1 to 4, ensuring that the application was uniform and the application amount was the same, and then left to stand for 1 hour. The concrete samples of Examples 1 to 4 were irradiated with an ultraviolet lamp (UV-A lamp with a wavelength of 365nm) to simulate the ultraviolet radiation under natural sunlight, and the ultraviolet intensity was controlled at 50 to 100Mw / cm 2 The test lasted for 3 h and the degradation results were evaluated gravimetrically (measuring the mass of oil removed).
[0097] 2. Experimental Results
[0098] The results are shown in Table 1.
[0099] Table 1 Test results of concrete material properties in various embodiments
[0100]
[0101]
[0102] It can be seen from Table 1 that the concrete material prepared by the present invention has suitable flow properties and moderate printability, and is more suitable for UAV 3D printing operations.
[0103] Experimental Example 2
[0104] This experimental example is used to verify the superiority of the concrete material formula of the present invention.
[0105] 1. Experimental Methods
[0106] 1. Printability
[0107] (1) Liquidity
[0108] According to the "Determination of fluidity of cement mortar" GB / T 2419, the concrete materials of Example 3 and Comparative Examples 1 to 9 were tested respectively within 25±1s, and the average diameters of the mortar in two vertical directions were unfolded after the jumping table jumped 25 times, so as to indicate the fluidity.
[0109] (2) Extrudability
[0110] The concrete materials of Example 3 and Comparative Examples 1 to 9 were used to continuously print a tear-free printed strip with a length of ≥2000 mm and a layer thickness of ≥10 mm. The width and thickness of the printed strip at 5 different positions with an interval of not less than 200 mm were measured, and the average value was calculated to indicate the extrudability.
[0111] (3) Opening hours
[0112] Using the concrete mixtures of Examples 1 to 4, strips with a length of ≥2000 mm were printed at intervals of 10 minutes, and the time corresponding to when the printed strips were interrupted or discontinuous was recorded to indicate the open time.
[0113] (4) Constructivity
[0114] The concrete materials of Example 3 and Comparative Examples 1 to 9 were used to continuously print two layers of closed loops, and the highest height of the printed body before collapse or deformation occurred was measured to indicate the constructability.
[0115] 2. Strength performance
[0116] A universal testing machine was used to perform stress tests on the concrete specimens obtained from the concrete materials of Example 3 and Comparative Examples 1 to 9, with a loading mode of 50 n / s.
[0117] 3. Self-cleaning performance
[0118] The organic pollutants (1g oil) were applied to the concrete samples of Example 3 and Comparative Examples 1 to 9, ensuring that the application was uniform and the application amount was the same, and then left to stand for 1 hour. The concrete samples of Example 3 and Comparative Examples 1 to 9 were irradiated with an ultraviolet lamp (UV-A lamp with a wavelength of 365nm) to simulate the ultraviolet radiation under natural sunlight, and the ultraviolet intensity was controlled at 50 to 100Mw / cm 2 The test lasted for 3 h and the degradation results were evaluated gravimetrically (measuring the mass of oil removed).
[0119] 2. Experimental Results
[0120] The results are shown in Table 2.
[0121] Table 2 Comparison of concrete material performance tests between Example 3 and Comparative Examples 1 to 9
[0122]
[0123]
[0124] As can be seen from Table 2, the present invention designs a 3D printing concrete material suitable for UAVs by optimizing the composition of 3D printing concrete materials; and uses spherical (ultrafine mineral microbeads) mineral admixtures and various admixtures, and adds graphene and nanoparticles at the same time. Since the printing materials required by UAVs are different from traditional materials, ultrafine mineral microbeads improve the adverse effects of traditional 3D printing concrete on UAV 3D printing, and improve the printability of 3D printing concrete materials. Various admixtures work together to adjust the working performance of concrete materials. The introduction of graphene mainly improves the mechanical properties and crack resistance of concrete, and enhances the density of cement paste and improves its impermeability through its flaky structure. Nanoparticles provide the self-cleaning function of concrete through their photocatalytic effect, while greatly improving the compressive strength. The high conductivity of graphene helps the transmission of electrons in the photocatalytic process, reduces the recombination of electron-hole pairs, and thus enhances the photocatalytic efficiency of nanoparticles. The high strength of graphene and the self-cleaning function of nanoparticles can be combined to create a concrete structure that is both durable and able to keep the surface clean. At the same time, the two-dimensional structure of graphene can help the nanoparticles to be more evenly distributed in the concrete matrix and reduce agglomeration. This uniform distribution at the nanoscale can maximize the reaction efficiency and material performance of the nanoparticles. The mix ratio of the present invention is more suitable for the operation mode of drones. It has made great improvements in physical properties while ensuring the strength of the material, so that the 3D printed concrete material can still maintain the sustainability of printing and good construction under the condition of high fluidity.
[0125] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A drone 3D printing concrete material, characterized in that: The invention comprises the following raw materials in parts by weight: 20 to 45 parts of cement, 5 to 15 parts of fly ash, 16 to 40 parts of sand and gravel, 1 to 10 parts of ultrafine mineral beads, 0.5 to 15 parts of mineral powder, 0.5 to 2.5 parts of water reducing agent, 0.01 to 0.05 parts of thickening rheological agent, 0.1 to 1 parts of early strength agent, 0.02 to 0.05 parts of defoaming agent, 0.1 to 0.5 parts of graphene, 0.5 to 2 parts of nano titanium dioxide particles and 20 to 30 parts of water.
2. The drone 3D printing concrete material according to claim 1, characterized in that: The cement is silicate cement with a strength grade of ≥42.5 and a specific surface area of 300-400m 2 / kg.
3. The drone 3D printing concrete material according to claim 1, characterized in that: The fly ash is secondary fly ash with a fineness of 14 to 25 μm.
4. The drone 3D printing concrete material according to claim 1, characterized in that: The sand and gravel are machine-made sand with a particle size range of 0.075-5.0 mm and an apparent density of 2000-2900 kg / m 3 .
5. The drone 3D printing concrete material according to claim 1, characterized in that: The ultrafine mineral microbeads have a fineness of d50≤3μm, a water content of 0.1% to 1.0%, a 0.045mm sieve residue of 5% to 10%, and a water requirement ratio of 80% to 98%; The mineral powder density is 2.5-3.5 g / cm 3 , specific surface area 500~650m 2 / kg, fluidity ratio 95% ~ 110%, water content 0.3% ~ 0.9%.
6. The drone 3D printing concrete material according to claim 1, characterized in that: The water reducing agent is a polycarboxylic acid type water reducing agent with a solid content of 30% to 50% and a water reducing rate of 20% to 50%; The thickening rheological agent is a mixture of a cellulose sodium salt thickening rheological agent and xanthan gum in a ratio of 1:1; wherein the viscosity of the cellulose sodium salt is 90000-120000 mPa·s, and the drying weight loss rate is ≤6.0%; and the viscosity of a 1% aqueous solution of xanthan gum is ≥500 mPa·s; The early strength agent is a mixture of one or more of sodium sulfate, calcium formate, sodium carbonate and gypsum, with a moisture content of ≤5.0% and a 1.18mm sieve residue of ≤1.0%; The defoamer is a polyether defoamer, and the mass concentration of the solution is 0.2-0.5 parts per thousand.
7. The drone 3D printing concrete material according to claim 1, characterized in that: The graphene is a two-dimensional material composed of a single layer of carbon atoms, with a size of less than 5 μm and a water content of 0.1% to 0.5%.
8. The drone 3D printing concrete material according to claim 1, characterized in that: The particle size of the nano titanium dioxide particles is 10-100 nm, and the water content is ≤0.5%.
9. A method for preparing a UAV 3D printing concrete material according to any one of claims 1 to 8, characterized in that: The steps include: (1) Add the formulated amount of cement, fly ash, sand and gravel, ultrafine mineral beads, and mineral powder into a blender and pre-mix for 50 to 80 seconds to obtain a mixed material A; (2) Add the formulated amount of water reducer, early strength agent and defoamer into the formulated amount of water and stir for 60 to 80 seconds to obtain a mixed material B; (3) After mixing the mixed material A and the mixed material B, add the thickening rheological agent in the formula amount and continue stirring for 60 to 90 seconds; (4) Continue to add the pre-prepared graphene and nano-titanium dioxide particles and stir for 60 seconds to obtain the desired drone 3D printing concrete material.
10. Use of the drone 3D printing concrete material according to any one of claims 1 to 8 in drone 3D printing.